ANALISIS PENGARUH EARNING PER SHARE (EPS) TERHADAP HARGA SAHAM - EVE IDA MALAU; Debora Silvia Hutagalung; Ambo Enre (SEKOLAH TINGGI AKUNTANSI DAN MANAJEMEN INDONESIA (STAMI), 2021)
The research objective was to determine the effect of earning per share of the stock price LQ-45 at the Indonesia Stock Exchange for the period 2016-2018. The research method used in analyzing the effect of earnings per share on the stock price is to use a simple regression analysis test and test (one-sample T test). The results obtained from this study indicate that there is significant influence between the earning per share on stock prices.